(untitled) (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2023)
A large-scale commercial production trial was conducted to evaluate the effect of supplemental 25-hydroxycholecalciferol (25(OH)D3) on the growth performance of broilers. A total of 100,000 day-old mixed-sex Cobb 500 broilers were allocated equally to 20 farms with 5000 broilers each. Two experimental diets were prepared: 1) Control diet [(3000 IU D3 kg diet-1 + 2760 IU D3 kg diet-1) = total 5760 IU D3 kg diet-1] and 2) Experimental diet [(3000 IU D3 kg diet-1 + 69 mcg 25(OH)D3 kg diet-1 = 2760 IU D3 equivalent kg diet-1) = total 5760 IU D3 kg diet-1]. The design used a randomized block design with Multivariate Analysis of Covariance analysis method The results showed that broilers chickens fed supplemental 25(OH)D3 significantly gained faster, more efficient feed conversion and lower mortality rate from 0 to 14 days when compared to those fed without 25(OH)D3 supplementation. Moreover, the relative growth on the diet supplemented with 25(OH)D3 at 7 days was significantly (p<0.05) greater than that without supplementation. At 14 days to harvest, growth parameters including the Production Efficiency Index of broilers supplemented with 25(OH)D3 were 3-4% better than that of the control diet. Significantly lower mortality rates (p<0.05) were observed in broilers fed 25(OH)D3-supplemented diets compared to unsupplemented diets. It can be concluded of this study demonstrated the positive impact of supplemental 25(OH)D3 on broilers raised under commercial conditions in West Java, Indonesia. Key words: broiler performance, commercial condition, mortality, 25 hydroxycholecalciferol